An attempt to determine the determinants of an effective impact of corporate social responsibility on consumer behaviour. A pilot study report = Próba określenia uwarunkowań skutecznego oddziaływania społecznej odpowiedzialności biznesu na zachowanie konsumenta. Komunikat z badania - Spodarczyk, Edyta (Zielona Góra: Faculty of Economics and Management Press)
It is assumed that the idea of corporate social responsibility implemented by an enterprise will be appreciated by consumers. Consumers will be more willing to choose offers and support initiatives of socially responsible companies. Social responsibility, as a distinguishing mark used in positioning an enterprise (brand), also aims to contribute to building the loyalty of consumers who will be characterised, among others, by lower price sensitivity, and in their purchasing decisions they will be guided by the company?s positive image.
Keywords: społeczna odpowiedzialność organizacji; zachowanie konsumenta; lojalność konsumentów; marka przedsiębiorstwa; corporate social responsibility; consumer behaviour; consumer loyalty; company brand